Risk and Return of Illiquid Investments: A Trade‐off for Superannuation Funds Offering Transferable Accounts. Issue 295 (4th August 2015) - Cummings, James R.; Ellis, Katrina
Abstract : This paper examines the pattern of investment by Australian defined‐contribution superannuation funds in illiquid assets, using a unique but confidential database. Not‐for‐profit funds allocate more of their portfolios to illiquid assets, on average, than retail funds. Their allocations reflect fund size, net cash inflows and member age – factors relevant to a fund's liquidity requirements. Furthermore, the allocations reflect the extent of the fund's in‐house investment management. In contrast, there is no clear relationship between these factors and allocations by retail funds. Funds with more illiquid investments experience investment returns that are commensurate with the non‐diversifiable risk these assets contribute to their overall portfolios.